Accounting, auditing and managerial control for sustainability - Songini, Lucrezia; Pistoni, Anna.; Herzig, Christian (Bingley, U.K. : Emerald, 2013)
Sustainability performance measurement and communication play a central role in supporting the implementation of the sustainability strategy, embedding sustainability into day-to-day operations and decision making, and developing relationships with stakeholders based on trust, transparency, and legitimacy. The purpose of this book is to explore new challenges and new prospects for sustainability accounting research and to discuss future directions of research. It considers a large spectrum of different theoretical lenses and research methods, and explores various types of organizational settings and practices in different countries. This book brings together articles that consider the main areas of accounting: financial accounting, auditing and managerial accounting, in order to critically review and advance theorizations and methodological applications to the study of all main accounting fields in a sustainability context. It aims to interest a quite large number of active researchers, professors and practitioners (CPAs and CMAs, managers and executives, but also consultants), both from the accounting field, and from the sustainability and CSR domains.
Introduction / Lucrezia Songini, Anna Pistoni, Christian Herzig -- Corporate social responsibility determinants : the relation with CSR disclosure / Anna Pistoni, Lucrezia Songini -- Determinants of corporate social disclosure through a multi-perspective approach : evidences from the target companies of socially responsible funds / Francesco Gangi, Carmen Trotta -- How SMEs disclose their sustainability performance. Which variables influence the choice of reporting guidelines? / Simone Domenico Scagnelli, Laura Corazza, Maurizio Cisi -- Water management and accounting : remarks and new insights from an accountability perspective / Silvana Signori, Gerald Avondo Bodino -- A review of the empirical research in management control, strategy and sustainability / Nathalie Crutzen, Christian Herzig -- Environmental management accounting systems : a review of the evidence and propositions for future research / Giovanni Battista Derchi, Michael Burkert, Daniel Oyon -- The use of causal mapping in the design of sustainability performance measurement systems : evidence from Novo Nordisk / Cristiana Parisi -- In control of sustainability information : untangling the role of accountants / Stefan Schaltegger, Dimitar Zvezdov.
Print version record
Keywords: Accounting; Management accounting & bookkeeping; Social responsibility of business; Sustainability; Environmental auditing; Managerial accounting; Corporations -- Auditing